Pattern of dermatological involvement in early postmenopausal period: a cross sectional study - Shah, Bhavika; Patvekar, M. A.; Singh, Pallavi; Deora, M. S.; ., Alisha (International Journal of Research in Dermatology, 2020)
Background: The high burden of menopausal symptoms notwithstanding, there is a paucity of published work evaluating its impact specifically on the skin and mucosa. With high incidence of underreported cases in developing countries, active screening of all women is essential for accurate assessment of prevalence of cutaneous features, as highlighted by this study. The objective of this study is to assess clinical patterns of dermatosis in menopausal women. Methods: A cross‑sectional study conducted in the dermatology department conducted on postmenopausal patients below 65 years having dermatoses after taking their written consent. Data analysis using SPSS 20.0. Results: Of 350 postmenopausal women, 165 had genital involvement, atrophic vaginitis (41.21%) being the most common manifesting typically as vaginal dryness. Of 82 women having oral complaints, 42.7% women had complaints of pain or difficulty swallowing in the absence of mucosal lesions. Of the total sample size, 34% women had had female pattern hair loss, maximum women with grade I-2 (45.4%) and I-3 (36.13%). Two key findings which we did not find previous records of included incidence of keratoderma climactericum (2.29%) and hirsutism in early menopause which we found to be 8%. It is important to note that only 28% of women were aware that their complaints were related to menopause or chose to seek active treatment for existing complaints. Conclusions: This study highlights the various clinical patterns of postmenopausal dermatoses to raise awareness in dermatologists and gynecologists for prompt diagnosis, treatment and patient education.